Recent advances of myotubularin-related (MTMR) protein family in cardiovascular diseases - Wang, Jia; Guo, Wei; Wang, Qiang; Yang, Yongjian; Sun, Xiongshan (Frontiers in Cardiovascular Medicine, 2024)
Belonging to a lipid phosphatase family containing 16 members, myotubularin-related proteins (MTMRs) are widely expressed in a variety of tissues and organs. MTMRs preferentially hydrolyzes phosphatidylinositol 3-monophosphate and phosphatidylinositol (3,5) bis-phosphate to generate phosphatidylinositol and phosphatidylinositol 5-monophosphate, respectively. These phosphoinositides (PIPs) promote membrane degradation during autophagosome-lysosomal fusion and are also involved in various regulatory signal transduction. Based on the ability of modulating the levels of these PIPs, MTMRs exert physiological functions such as vesicle trafficking, cell proliferation, differentiation, necrosis, cytoskeleton, and cell migration. It has recently been found that MTMRs are also involved in the occurrence and development of several cardiovascular diseases, including cardiomyocyte hypertrophy, proliferation of vascular smooth muscle cell, LQT1, aortic aneurysm, etc.This review summarizes the functions of MTMRs and highlights their pathophysiological roles in cardiovascular diseases.